2017
DOI: 10.1021/acs.langmuir.6b04602
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Segregation and Complexation in Amphiphilic Copolymers by Architecture and Confinement

Abstract: Segregation is a well-known principle for micellization, as solvophobic components try to minimize interactions with other entities (such as solvent) by self-assembly. An opposite principle is based on complexation (or coacervation), leading to the coassembly/association of different components. Most cases in the literature rely on only one of these modes, though the classical micellization scheme (such as spherical micelles, wormlike micelles, and vesicles) can be enriched by a subtle balance of segregation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 97 publications
1
36
0
Order By: Relevance
“…As in our previous work, the star polymers were modeled with a simple bead spring model in which each effective monomer was described as a bead. The star polymers consist of three different types of beads: A, B, and C beads.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As in our previous work, the star polymers were modeled with a simple bead spring model in which each effective monomer was described as a bead. The star polymers consist of three different types of beads: A, B, and C beads.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…For bead type combinations of the type A‐B (or B‐A) the interaction parameter εij was set to εA-B=0.6 knormalBT. The value of εA-B was obtained from previous work where it was found that under these conditions a weak complex is formed. For all other bead combinations: εij=0.0 knormalBT. Bead Segregation : In this case, the B beads attract each other to segregate from the A beads.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerizing NIPAM [22] in the presence of a soluble poly(dimethyl acrylamide) (PDMAM) macro-CTA, results in diblock copolymers which undergo spontaneous self-assembly due to the segregated [23] PNIPAM component (when synthesis conducted above LCST). [24] Unfortunately, these nano-objects could not conveniently be studied in a non-equilibrium state as the PNIPAM required crosslinking to avoid unimolecular dissolution at ambient temperature.…”
Section: Main Textmentioning
confidence: 99%